Analisis Keputusan Konsumen Dalam Menggunakan Jasa Layanan Perbankan Syariah - Mahfud Nugroho; Muzakar Isa; Imronudin . (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
The aim of this article was to analyze the influence of office location, promotion, religiosity and rate of return on consumer decisions using Islamic banking services. This type of research is quantitative research. The study population is all consumers in Islamic banks located in Jakarta, while the study sample is consumers of Islamic banks taken randomly from several Islamic banks in Jakarta. The sampling technique uses accidental sampling. Retrieval of data uses a questionnaire. The analyticaltool used is multiple linear regression analysis. The results showed that location, promotion, level of religiosity, and rate of return had a positive and significant effect on consumer decisions in choosing services at Islamic banks. The level of return is the variable that has the most influence for consumers to use Islamic banking services